A Role for the Brain RAS in Alzheimer’s and Parkinson’s Diseases - Wright, John W.; Kawas, Leen H.; Harding, Joseph W. (Frontiers in Endocrinology, 2013)
The brain renin-angiotensin system (RAS) has available the necessary functional components to produce the active ligands angiotensins II, III, IV, angiotensin (1-7), and angiotensin (3-7). These ligands interact with several receptor proteins including AT1, AT2, AT4 and Mas distributed within the central and peripheral nervous systems as well as local RASs in several organs. This review first describes the enzymatic pathways in place to synthesize these ligands and the binding characteristics of these angiotensin receptor subtypes. We next discuss current hypotheses to explain the disorders of Alzheimer’s disease (AD) and Parkinson’s disease (PD), as well as research efforts focused on the use of angiotensin converting enzyme (ACE) inhibitors and angiotensin receptor blockers (ARBs), in their treatment. ACE inhibitors and ARBs are showing promise in the treatment of several neurodegenerative pathologies; however, there is a need for the development of analogues capable of penetrating the blood-brain barrier and acting as agonists or antagonists at these receptor sites. Angiotensins II (AngII) and IV (Ang(IV) have been shown to play opposing roles regarding memory acquisition and consolidation in animal models. We discuss the development of efficacious AngIV analogues in the treatment of animal models of AD and PD. These AngIV analogues act via the AT4 receptor subtype which may coincide with the hepatocyte growth factor (HGF)/c-Met receptor system. Finally, future research directions are described concerning new approaches to the treatment of these two neurological diseases.